Oxymetazoline Inhibits and Resolves Inflammatory Reactions in Human Neutrophils - Beck-Speier, Ingrid (J Pharmacol Sci, 2009)
The nasal decongestant oxymetazoline (OMZ) exhibits anti-oxidative and antiinflammatory properties (I. Beck-Speier et al., J Pharmacol Exp Ther. 2006;316:842–851). In a follow up study, we hypothesized that OMZ generates pro-resolving lipoxins being paralleled by production of immune-modulating prostaglandin E(2) (PGE(2)) and anti-inflammatory 15(S)-hydroxy-eicosatetraenoic acid [15(S)-HETE] and depletion of pro-inflammatory leukotriene B(4) (LTB(4)). Human neutrophils (PMN) were chosen as the cellular system. The effect of OMZ on these parameters as well as on respiratory burst activity and oxidative stress marker 8-isprostane was analyzed in unstimulated and co-stimulated PMN by ultrafine carbon particles (UCP) or opsonized zymosan (OZ), respectively. In unstimulated cells, OMZ induced formation of PGE(2), 15(S)-HETE, and LXA(4). The levels of LTB(4) and 8-isoprostane were not affected, whereas respiratory burst activity was drastically inhibited. In UCP- and OZ-stimulated control cells, all parameters were elevated. Here, OMZ maintained the increased levels of PGE(2), 15(S)-HETE, and LXA(4), but substantially suppressed levels of LTB(4) and 8-isoprostane and inhibited the respiratory burst activity. These findings suggest a switch from the pro-inflammatory eicosanoid class LTB(4) to the pro-resolving LXA(4). Since LXA(4) is most relevant in returning inflamed tissue to homeostasis, OMZ is postulated to terminate rhinitis-related inflammation, thus contributing to shortening of disease duration.